THE ROLE OF THE N.V. SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE IN THE CREATION OF DISASTER MEDICINE IN THE COUNTRY - M. S. Khubutiya; Y. S. Goldfarb; V. N. Aleksandrovsky; M. M. Abakumov; S. A. Kabanova (Неотложная медицинская помощь)
The occurrence  of large-scale emergencies with great  human  losses  and the  absence of a unified authority  of the country health  system which would manage  its medical and sanitary consequences required  the  creation  of special  units to provide emergency  health  services (EHS) in mass injuries. The disaster  medicine  became  attractive for the N.V. Sklifosovsky Research  Institute  for Emergency Medicine in the 70s of the last century. Originally, the Department for Disaster Medicine was established at the  Institute  in 1987. At the  Department, the  extensive  work was performed  to shorten  a time gap between the delivery of medical care and the beginning  of a disaster  as much as possible. It was based  on a created  concept  for organization of medical  assistance and evacuation,  methods of its expertise and the  development of technical  means  for phased  medical  and evacuatiol  support of victims. The organizational and medical-diagnostic specificity of EHS in emergencies and its delivery were analyzed  in order to reduce  the severity of consequences. The health  care experience in emergencies has been  enriched  by the staff of the Institute  (who were not employees  of the Department)  actively involved in the management of mass injuries and poisonings via air ambulance at the accident site and in the treatment of victims admitted to the Institute  from sites of emergencies. Consequently, the N.V. Sklifosovsky Research Institute  for Emergency Medicine developed and offered the  scientific and organizational basis  for EHS in emergencies which made  a significant  practical contribution to the creation  of public services for disaster  medicine in the country.